Evaluation of the reduction in perceived and performance fatigability by functional compression tights during squat exercises via electromyography and electroencephalography analysis - Takuma Isshiki; Shinnosuke Tsukada; Minami Akao; Yuna Ishikura; Hayato Shigetoh; Takayuki Kodama; Junya Miyazaki (PLoS ONE, 2025)
Objectives Functional compression tights are widely used to support muscle activity, enhance blood flow and reduce fatigue, which comprises performance (motor or cognitive) and perceived fatigability. Although previous studies have reported their effects on motor performance fatigability, little is known about their effects on cognitive performance fatigability or brain activity. This study aimed to evaluate quantitatively and comprehensively the effects of functional compression tights on perceived fatigability, muscle activity, and electroencephalographic (EEG) responses. Methods Twenty healthy young adults performed squat tasks under two conditions (with and without functional compression tights) using a crossover design. Muscle activity was measured using surface electromyography (EMG) of the five thigh muscles to calculate the root mean square (RMS) and mean frequency (MF). EEG activity was recorded in the Fp1, Fp2, and Fz regions, and power change rates in the alpha, beta, and theta bands were calculated. Perceived fatigability was assessed using a numerical rating scale. Wilcoxon signed-rank tests were used for between-condition comparisons, and Spearman’s rank correlation coefficients were calculated to examine the comprehensive relationships among perceived fatigability, muscle activity, and EEG activity. Results Wearing tights significantly reduced perceived fatigability (p = 0.003) and RMS of the vastus medialis obliquus (VMO) (p = 0.041). Although not statistically significant (p = 0.054), the moderate effect size suggests a stabilizing effect of functional compression tights on frontal EEG activity. Under the condition with functional compression tights, the RMS of the RF positively correlated with perceived fatigability (ρ = 0.53), while MF showed a negative correlation (ρ = –0.70). Positive correlations were also observed between perceived fatigability and the alpha/theta powers at Fp2 and alpha power at Fz. Discussion Wearing functional compression tights may alleviate motor and cognitive performance fatigability by stabilizing muscle and frontal brain activity. These findings support its utility in managing motor and cognitive fatigability during physical activity.